PERFORMANCE OF BROILER CHICKEN ON TWO REARING SYSTEMS (Indian Journal of Animal Production and Management, 2015)
240 day-old commercial broiler chicks of Vencob strain was randomly divided into 4 groups i.e. two groups each for hover (Groups 1 and 2) and battery (Groups 3 and 4) types of brooding. All groups were sub divided into 4 replicates each with 15 chicks in per replicate. They were reared with standard feeding and hygienic management. On 22 day, 60 birds each from hover (Group 1) and battery (Group 4) brooding were subjected to deep-litter system of rearing and designated as T1 and T2, respectively. Similarly, 60 birds each from hover (Group 2) and battery (Group 3) brooding were subjected to cage system of rearing and designated as T3 and T4, respectively and were reared for 42 days. Mean body weight was significantly (P < 0.05) better in T3 as compared to other groups. Feed consumption was significantly (P < 0.05) lower in T4 as compared to other groups. Gain in body weight did not differ irrespective of treatments. Feed conversion efficiency (FCE) and performance index were significantly (P < 0.05) better in T3 than other groups. Other parameters like liveability, carcass characteristics, dressing percentage and net profit was better in caged birds. From the results, it can be concluded that the performance in terms of growth, feed consumption, FCE, performance index and net profit was better in cage system than deep litter systems of rearing.
Keywords: Carcass; deep-litter; feed conversion efficiency; performance index